A GIS based assessment of the relationship between housing conditions and rental value in government built housing Estates in Minna - Ajayi, M.T.A.; Nuhu, M.B.; Bello, M.Z.; Shuaib, S.I.; Owoyele, G.; Onuigbo, I.; Babalol, A.; Alias, A. (Penerbit UKM, 2015)
Housing management decisions require consideration of location and space. There is a constant need for more technology and training in the industry and Geographic Information System (GIS) is not known to have been used in tackling the problems of housing conditions and related problems in Minna. This study examines the relationship between housing conditions and rental value of selected housing estates in Minna with the aid of GIS. Census sample technique was adopted where all the houses in the housing estates were sampled. Satellite images of M.I. Wushishi Housing Estate, Bosso Estate and Oduoye Housing Estate were geo-referenced and maps were produced for various analysis. Conventional geo-database was created for conditions of houses in the housing estates and from it geo-statistical analyses was carried out which produce kriging and spatial autocorrelation analysis. In addition, correlation analysis was used to analyse the impact of building conditions on rental value. It was found out among others that building conditions has weak relationship with rental values in the housing estates. It was therefore recommended amidst others that Geo-statistical tools should be an instrument for measuring and monitoring of residential property development.